Length–weight relationships and condition factors of several endemic and native species of the genera Alburnoides, Alburnus and Squalius - Kurtul Irmak; Kaya Cüneyt; Onay Hatice; Bayçelebi Esra; Turan Davut (Oceanological and Hydrobiological Studies, 2024)
The present study examined for the first time both length–to–weight relationships and condition factors of ten species belonging to three endemically rich genera: Alburnoides (nspecimens = 361), Alburnus (nspecimens = 36), and Squalius (nspecimens = 205). Fish were sampled in several lakes and streams using electroshocking. Fish samples ranged from 3.60 cm to 27.40 cm in total length and from 38.00 g to 250.02 g in total weight. The coefficient of determination for all populations was R2 ≥ 0.95, while the b value varied between 3.0158 and 3.4957 for all sampling locations. The latter ranged from 3.0158 to 3.4957 for Alburnoides, from 3.0357 to 3.2327 for Alburnus, and from 3.0743 to 3.2143 for Squalius populations. Fulton’s condition factor was calculated for all populations. The research presented here focused on data-deficient endemic and native species of Anatolian freshwater resources, and the results obtained may prove useful in biodiversity management strategies.